Programmes and Practices in Contextualising the Curriculum for Primary School Students - K.M., SOFIA; K., ANIL KUMAR (THE PRIMARY TEACHER, 2015)
The term “localising” (or contextualising) curriculum has become a central concept in primary education. The National Curriculum Framework (NCF, 2005) has clearly stated it as of situating learning in the context of the child’s world, and of making the boundary between the school and its natural and social environment porous (p.30). This attempt at contextualising curriculum to improve the quality of education becomes imperative for those who have not benefitted from the traditional curriculum. The present study is set in the primary schools in the coastal area of Beypore of Calicut district in Kerala. By focussing on localising curriculum, the researcher explores the programmes made by the educational functionaries, and the practices adopted by the schools and teachers for contextualising the curriculum. The study also concerns the participation and the responses of learners and their parents about the need for a shift from general textbook-based instruction to the localised text in primary classes recommended by NCF (2005) for a more participatory localised curriculum. It concludes by stressing the immediate need of contextualising the curriculum for a meaningful and efficient teaching-learning process, and for decentralised planning and programmes to materialise it.